A narrative 3-phase 9-level voltage source inverter - M. Selvaperumal; D. Kirubakaran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
A tale technique for a 3-stage nine-level voltage source inverter utilizing sixteen switches is presented. The given system utilizes ordinary 3-stage scaffolds of two-level as a diode braced model. A DC interface voltage is provided so that the fell H-connect produces the nine voltage levels. The exchanging designs are expressed as the levels expand then the example is hard to create three-stage yields with key balance procedures. Here an answer for an a-level inverter to create required voltage-level with less power electronic parts by setting up in the look-into tables. This investigation diagrams the correlations between nine-level voltage source inverters in various arrangements and proposed novel, sixteen switch three-stage inverter structured with a smaller number of intensity electronic parts and reenacted in MATLAB/Simulink.